Lipase Producing Potential of Different Bacteria Species Isolated from Cooking Oil Contaminated Soils - Fakorede, C. N.; Itakorode, B. O.; Olayiwola, A. T.; Anifowose, T. E. (International Journal of Environment, Agriculture and Biotechnology, 2019)
n this study, we investigated the lipolytic activity of different bacteria strains isolated from different cooking oil contaminated soils.This was with a view to finding the isolate with the highest lipase-producing potential.A total of 70 bacteria strainswere isolated from the soil samples and the morphological examination of each isolate was done and characterized. 20 bacterial isolates were screened for lipase activity using chromogenic composed medium and the lipase producing microorganisms produced clear zones on this media. The isolate showing maximum activity was identified as Pseudomonas sp using Berger’s manual. The result showed that Pseudomonas sp. has the highest lipase activity with the largest diameter of 20.4 mm, 20.4 mm and 20.9 mm at 24, 48 and 72 hours of incubation while Escherichia coli, Klebsiella sp., Alcaligens sp., Citrobacter sp., Streptococcus sp., and Serratia sp. showed no lipase activity with 0.00 mm within the hours of incubation.The prevalence of lipase activity of each suspected bacterial isolate was investigated. Pseudomonas sp. has the highest prevalence of lipase activity with a value of 32.3% and the bacterial isolates with the lowest prevalence rate include Klebsiellasp, Escherichia coli, Serratia sp., Citrobacter sp., Streptococcus sp., and Alcaligens sp. with 4.2% each.. Staphylococcus sp. has a prevalence rate of 21.2%, Bacillus sp. with 6.1% prevalence rate while Bifidobacterium sp. and Corynbacterium sp. has 7.6% each.